World philosophies - "Smart, Ninian" (London, 1999)
This is a collection of stories of philosophy and religion from around the world. The author discusses figures such as: Plato and Kierkega ard in the West; the Buddha and Mao Zedong in Asia; temples and Knibanga in Africa; and Rodo and Royce in America. It also includes ideas such as: Indian ideas of testimony and evidence; Chinese notions of moral development; Buddhist concepts of cosmology; and Latin American critiques of materialism.
Keywords: Philosophy history